2021
DOI: 10.32539/bsm.v5i8.341
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Congenital Deafness in Pediatric Patients Who Underwent Otoaccoustic Emission (OAE) and Auditory Brainstem Response (ABR) Examinations in General Hospital Mohammad Hoesin Palembang, Indonesia

Abstract: Introduction: Congenital deafness is a hearing loss that occurs at birth. Congenital deafness in neonates can be caused by risk factors during pregnancy and during the birth process. The tests carried out for hearing screening for neonates in hospital up to 1 month old are Otoaccoustic Emission (OAE) and Auditory Brainstem Response (ABR) examinations. Objective: Determining the relationship between family history of deafness, syndromes associated with sensorineural hearing loss, TORCH infection and prena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The current study found that newborns with hyperbilirubinemia, a family history of hearing loss, and intrauterine infections may pass the OAEs test but receive a refer result from AABR. These risk factors are significant for hearing loss [17,[19][20][21]. TEOAEs aim to assess the integrity of the cochlea's outer hair cells, which cannot detect hearing loss involving damage to the brain or central auditory system [1].…”
Section: Teoaesmentioning
confidence: 99%
“…The current study found that newborns with hyperbilirubinemia, a family history of hearing loss, and intrauterine infections may pass the OAEs test but receive a refer result from AABR. These risk factors are significant for hearing loss [17,[19][20][21]. TEOAEs aim to assess the integrity of the cochlea's outer hair cells, which cannot detect hearing loss involving damage to the brain or central auditory system [1].…”
Section: Teoaesmentioning
confidence: 99%